Cigarette Smoke Exposure Inhibits Bacterial Killing via TFEB-Mediated Autophagy Impairment and Resulting Phagocytosis Defect - Garrett Pehote; Manish Bodas; Kathryn Brucia; Neeraj Vij (Hindawi Limited, 2017)
Introduction. Cigarette smoke (CS) exposure is the leading risk factor for COPD-emphysema pathogenesis. A common characteristic of COPD is impaired phagocytosis that causes frequent exacerbations in patients leading to increased morbidity. However, the underlying mechanism is unclear. Hence, we investigated if CS exposure causes autophagy impairment as a mechanism for diminished bacterial clearance via phagocytosis by utilizing murine macrophages (RAW264.7 cells) and Pseudomonas aeruginosa (PA01-GFP) as an experimental model. Methods. Briefly, RAW cells were treated with cigarette smoke extract (CSE), chloroquine (autophagy inhibitor), TFEB-shRNA, CFTR(inh)-172, and/or fisetin prior to bacterial infection for functional analysis. Results. Bacterial clearance of PA01-GFP was significantly impaired while its survival was promoted by CSE (p<0.01), autophagy inhibition (p<0.05; p<0.01), TFEB knockdown (p<0.01; p<0.001), and inhibition of CFTR function (p<0.001; p<0.01) in comparison to the control group(s) that was significantly recovered by autophagy-inducing antioxidant drug, fisetin, treatment (p<0.05; p<0.01; and p<0.001). Moreover, investigations into other pharmacological properties of fisetin show that it has significant mucolytic and bactericidal activities (p<0.01; p<0.001), which warrants further investigation. Conclusions. Our data suggests that CS-mediated autophagy impairment as a critical mechanism involved in the resulting phagocytic defect, as well as the therapeutic potential of autophagy-inducing drugs in restoring is CS-impaired phagocytosis.